Manganese-catalyzed C(sp(2))-H alkylation of indolines and arenes with unactivated alkyl bromides - Verma, Suryadev K.; Punji, Benudhar (Chemistry-an Asian Journal, 2022)
Selective C(sp(2))-H bond alkylation of indoline, carbazole and (2-pyridinyl)arenes with unactivated alkyl bromides is achieved using MnBr2 catalyst in the absence of an external ligand. The alkylation uses a simple LiHMDS base and avoids the necessity of Grignard reagent, unlike other Mn-catalyzed C-H functionalization. This reaction proceeded either through a five- or a less-favored six-membered metallacycle, and tolerated diverse functionalities, including alkenyl, alkynyl, silyl, aryl ether, pyrrolyl, indolyl, carbazolyl and alkyl bearing fatty alcohol and polycyclic-steroid moieties. Alkylation follows a single electron transfer (SET) pathway involving 1e oxidative addition of alkyl bromide and a rate-limiting C-H metalation.
Keywords: Alkylation; C-H activation; indoline; ligand-free; manganese

CuNPs@Al2O3-cellulose composite for the ligand-free Suzuki cross-coupling reactions in batch and continuous flow process - Patil, Seema; Rajmane, Archana; Jadhav, Sanjay; Rode, Chandrashekhar; Kumbhar, Arjun (Journal of Organometallic Chemistry, 2024)
In the present work, we synthesized recyclable CuNPs@Al2O3-CELL composite from an inexpensive and commercially available synthetic reagent by a simple method. The catalyst was characterized by various techniques such as TGA (Thermogravimetric analysis), SEM (Scanning electron microscope), TEM (Transmission electron microscopy), XPS (X-ray photoelectron spectroscopy), EDS (Energy dispersive spectroscopy), and AAS (Atomic Absorption Spectroscopy). The composite was applied for the Suzuki coupling reactions in the batch and flow process. The aryl halides were easily coupled with arylboronic acids in 95 % ethanol at 78 C. We systematically investigated the role of reaction temperature, solvent, and catalyst loading, on the transient and steady-state behavior of the flow reactor through an automated flow chemistry platform. The CuNPs@Al2O3CELL catalytic particles demonstrate minimal deactivation and leaching over a continuous Suzuki coupling reaction at a 20 min nominal residence time at 100 C. Moreover, the catalyst can be recovered by simple filtration and reused at least five times with a moderate decrease in product yield. The excellent activity and stability of the catalyst have been attributed to the strong chelation of the Cu species with hydroxyl functional groups of the Al2O3-CELL composite. The catalytic system was highly efficient in Suzuki coupling of various aryl bromides with different aryl boronic acids, yielding good to excellent product yields (80-96 %) with a TON of 15.914-19.066 and TOF of 2.649-9.533 h(-1).
Keywords: Continuous flow process; CuNPs@Al2O3-CELL; ligand-free; recyclable; Suzuki coupling